Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Percaya Diri Siswa (PTK pada Kelas V di Sekolah Dasar Negeri 52 Kota Bengkulu) - Ige Gusti Pratama; Alexon (JURIDIKDAS, 2023)
This study aims to determine the application of the Role Playing learning model to increase the confidence of students in class V B of SDN 52 Bengkulu City. The research subjects were teachers and students of class V B SDN 52 Bengkulu City. The research instrument was in the form of an observation sheet, which consisted of an observation sheet applying the Role Playing learning model and a student's confidence observation sheet. The data analysis technique uses the average score formula, highest score, lowest score, difference in score and range of values for each criterion. The average results of the implementation of the first cycle Role Playing learning model were obtained at 29.5 with sufficient categories and the second cycle obtained at 38.5 with a very good category. The results of the average self-confidence of the first cycle students were obtained at 19.03 with sufficient categories and the second cycle was obtained at 26.15 with very good categories. Based on the results of the t test obtained t0 6.25 is greater than t table 1.706. Then it can be concluded that the application of the Role Playing learning model can increase the confidence of students in class V B SDN 52 Bengkulu City.